Karakteristik Fisik dan Mikrostruktur Otot Semitendinosus pada Sapi Lokal dan Sapi Impor (PHYSICAL AND MICROSTRUCTURE CHARACTERISTICS OF SEMITENDINOSUS MUSCLE IN LOCAL CATTLE AND IMPORTED COWS) - Safitri, Aldina; Priyanto, Rudy; Adnyane, I Ketut Mudite; Nuraini, Henny (Jurnal Veteriner, 2019)
Semitendinosus muscle is widely used as raw material for traditional culinary in Indonesia. Studies on local beef cattle potency have been widely conducted, however there is limited information on physical and microstructures characteristics of semitendinosus muscle.  This study aimed to examine physical and microstructures characteristics of semitendinosus muscle from different breeds of local and import beef cattle.  This study used semitendinosus muscle from angus cross cattle, bali cattle, brahman cross cattle, PO cattle, and simmental X PO cattle, with age ranging from 18-30 months (I1-I2).  The results showed that semitendinosus muscle of local breed cattle could meet the criteria of physical characteristics of consumer demand in Indonesia. Based on perimysium thickness and fascicle area of the cross section of semitendinosus muscle, angus cross cattle and bali cattle had softer muscle texture compared to the other breeds.